FUNGSI RITUAL MENYAMBUT HARI RAYA NYEPI PADA ORANG BALI DI DESA LAMBODIJAYA KECAMATAN LALEMBUU KABUPATEN KONAWE SELATAN - Akhmad Marhadi; Tri Miarsih (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This study examines the function of rites performed by the Balinese in Lambodijaya village District of Lalembuu Southern Konawe in welcoming the Day of Silence. The objective of this study was to determine and to describe the process of implementation and functions of welcoming Nyepi ritual of Balinese in that region. This study applied a qualitative approach. Therefore, the process of data collection was done by means of field research. The data collected through in-depth interviews and observation. The ritual process consists of several stages, that are: a) the preparation for the ritual which includes the manufacture of ogoh-ogoh, manufacture ritual offerings; b) the implementation process of the ritual that consists of a series of specific rituals such as: Melasti ritual, mecaru ritual, panca sembah ritual, and pengrupukan. The ritual in welcoming the Day of Silence is a ritual that has many functions. Each stage of the ritual has their respective functions. Melasti ritual serves to cleanse the impurities present in humans, as well as cleaning stuff of temple in order they would be given strength or grace by God to live a life in subsequent years. Mecaru ritual is believed to be a harmonization of environmental ritual that human life can be balanced and buta kala, so the buta kala did not disturb people. Panca sembah ritual serves as a request for the maintenance of life, gets grace, salvation, and forgiveness of God. While pengrupukan serves to expel spirits that exist in the home environment and the rural environment, so that the people live in peace and harmony. Keywords: functions, rituals, Nyepi